SUFIS’ UNDERSTANDING ON TWENTY ATTRIBUTES OF ALLAH IN MA'DIN AL-ASRĀR FI MANHAJ AL-ABRĀR MANUSCRIPT (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
In Islamic history of Palembang, manuscript has contributed to the transmission of knowledge. Religious works was an achievement for the Muslim scholars in the past. One of Palembang's cultural heritage is the Ma'din al-Asrār manuscript. This text contains theological teachings. In terms of theology, Palembang's Muslim scholars adhered to the understanding of the nature of God. As with observations on theological works that talk about nature 20, it is found that the majority of his studies use the Kalam Science approach (reasoning approach). This is different from the description of the 20 characteristics contained in the Ma'din al-Asrār manuscript. The purpose of study is to analyse how Sufis understand on the 20 attributes of Allah. This article uses a library research, with the primary data source is the book Alih Aksara Naskah Ma'din al-Asrār Fi Manhaj al-Abrār (MAFMA). Data collection uses literature study, and data analysis uses text interpretation methods. This research concludes that the 20 attributes which is understood by the Sufis is more orientated to theological-sufistic, where the discussion of aqidah is attempted to feel it (żauq). For example, wujud they understood as a substance, ta’ayyunāt (entity), maẓhar (appearance), tajalliyāt (manifestation), aṡar (former or influence); qidam is understood by being which is not preceded by even nothingness ('adam); baqā' with azaliyah (a being that existed before something existed) and aḥadiyatu'Llāh (oneness of God, and except Him the call muqayyad (being dependent on others); mukhālafatuhū li al-ḥawadiṡ is denying everything except Him even  the being of human himself, and many other discussion.Dalam sejarah Islam di Palembang, naskah berkontribusi besar dalam transmisi keilmuan. Menulis masalah-masalah keagamaan menjadi satu prestasi bagi ulama-ulama silam. Salah satu satu warisan budaya tulis masa lampau Palembang adalah naskah Ma‘din al-Asrār. Naskah ini memuat ajaran-ajaran teologis. Dalam hal teologis, ulama-ulama silam Palembang menganut paham sifat 20 Allah. Sebagaimana pengamatan terhadap karya-karya teologi yang berbicara tentang sifat 20, didapati bahwa mayoritas kajian-kajiannya menggunakan pendekatan Ilmu Kalam (pendekatan akal). Hal ini berbeda dengan uraian sifat 20 yang terdapat di dalam naskah Ma‘din al-Asrār, dimana sifat tersebut mereka memahaminya dengan pendekatan sufistik. Tujuan penelitian ini adalah untuk memaparkan pemahaman ulama sufi terhadap sifat 20. Penelitian ini merupakan penelitian kepustakaan, dengan sumber data primer buku Alih Aksara Naskah Ma‘din al-Asrār Fi Manhaj al-Abrār (MAFMA). Pengumpulan data menggunakan studi literatur, dan analisa datanya menggunakan metode interpretasi teks. Penelitian ini menyimpulkan bahwa sifat 20 yang dipahami oleh kaum sufi lebih berorientasi pada teologis-sufistik, dimana pembahasan akidah diupayakan untuk merasainya (żauq). Misalnya wujud mereka pahami dengan zat, ta’ayyunāt, maẓhar (penampakan), tajalliyāt (manifestasi), aṡar (bekas atau pengaruh), bahkan wahm atau khayālī dapat dikategorikan juga sebagai wujud; qidam dipahami dengan wujud yang tidak didahului oleh ketiadaan sekalipun (‘adam); baqā’ dengan aḥadiyatu’Llāh (keesaan Allah) dan azaliyah, dan selain-Nya adalah wujud muqayyad (wujud yang bergantung dengan yang lain); mukhālafatuhū li al-ḥawadiṡ dipahami dengan menafikan segala sesuatu selain-Nya hingga pada diri manusia itu sendiri. dan lain-lain seterusnya.